The Effect of Brand Awareness, Word of Mouth and Product Quality on The Purchase Decision of Adidas Shoes in Surabaya - Egy Cahya Aryanda; Utomo, Priyo; Arifin, Syamsul; Nuryadi, Nuryadi; Farida, Nur (Jurnal Economic Resource, 2025)
This study investigates the influence of brand awareness, word of mouth, and product quality on purchasing decisions for Adidas shoes in Surabaya, with a focus on consumer behavior in the competitive sports fashion industry. Using a quantitative approach, data were collected from 385 respondents through non-probability sampling and analyzed using Partial Least Squares (PLS). The findings indicate that word of mouth and product quality have a significant impact on purchasing decisions, whereas brand awareness has no direct effect. The study is limited to Adidas consumers in Surabaya. Companies should enhance product design, comfort, and durability while strengthening consumer experiences and sustaining brand awareness as a long-term strategy.